Blood pressure variability in hypertension patients in Indian clinical settings. (4th February 2022) - Abhyankar, M; Jinghan, A K; Das, C; Datta, S; Goswami, A D; Silki, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background:  Blood pressure variability (BPV) is a potential predictor for complications such as coronary artery disease, heart failure, stroke, and all-cause death, independently of mean blood pressure (BP) in patients with hypertension.(1) Objective:  The survey was carried out to seek the opinion of Indian clinicians on the burden, measurement  and management of BPV in patients with hypertension. Method:  This PAN-India survey used a structured web-based objective questionnaire that was administered to 200 clinicians via google forms. The responses were analyzed descriptively. Results:  This study suggests that >80% of the clinicians reported that 10-40% of their hypertensive patients experience BPV while 13% and 6.5% respectively, reported having BPV issues in <10% and >40% of their patients. A large majority of the clinicians (88.5%) agreed that effective control of BPV in hypertensive patients exerts benefits to prevent complications like target organ damage, cardiovascular disease and mortality. A combination of home and office BP monitoring was the most recommended approach for the measurement of BPV by 28% of the clinicians, followed by home monitoring (23%) > ambulatory monitoring (22.5%) > combination of ambulatory and office monitoring (21%) > office monitoring (4.5%) of BP. A majority of clinicians opted for angiotensin receptor blocker (ARB) + calcium channel blocker (CCB), ARB + beta blocker (BB) and ARB + diuretic as most preferred antihypertensive combination for effective control of BP and BPV (Figure 1). In particular, the clinicians opined for Telmisartan + Amlodipine (45.5%) > Telmisartan + Chorthalidone (27%) > Telmisartan + Cilnidipine (14%) > Telmisartan + Hydrochlorothiazide (13%) as the preferred antihypertensive combinations. 41% and 30.5% of the clinicians reported that they would shift their patients with high BPV to a dual and a triple combination of antihypertensives, respectively followed by increasing the antihypertensive dose (18%) and shifting to new antihypertensive medication (8.5%). Conclusion:  The survey underlined the considerable prevalence of BPV in hypertensive individuals and that its control can be beneficial in reducing the risk of future complications. The study also reflects that both home and office BP monitoring are important to identify BPV while ARBs particularly, Telmisartan in combination with CCB or a diuretic is the preferred regimen for effective control of BP and BPV.